Declining antibody levels to Trypanosoma cruzi correlate with polymerase chain reaction positivity and electrocardiographic changes in a retrospective cohort of untreated Brazilian blood donors. - Lewis F Buss; Léa Campos de Oliveira-da Silva; Carlos H V Moreira; Erika R Manuli; Flavia C Sales; Ingra Morales; Clara Di Germanio; Cesar de Almeida-Neto; Sonia Bakkour; Paul Constable; Marcelo M Pinto-Filho; Antonio L Ribeiro; et al. (Public Library of Science (PLoS), 2020)
Background Although infection with Trypanosoma cruzi is thought to be lifelong, less than half of those infected develop cardiomyopathy, suggesting greater parasite control or even clearance. Antibody levels appear to correlate with T. cruzi (antigen) load. We test the association between a downwards antibody trajectory, PCR positivity and ECG alterations in untreated individuals with Chagas disease. Methodology/principal findings This is a retrospective cohort of T. cruzi seropositive blood donors. Paired blood samples (index donation and follow-up) were tested using the VITROS Immunodiagnostic Products Anti-T.cruzi (Chagas) assay (Ortho Clinical Diagnostics, Raritan NJ) and PCR performed on the follow-up sample. A 12-lead resting ECG was performed. Significant antibody decline was defined as a reduction of > 1 signal-to-cutoff (S/CO) unit on the VITROS assay. Follow-up S/CO of < 4 was defined as borderline/low. 276 untreated seropositive blood donors were included. The median (IQR) follow-up was 12.7 years (8.5-16.9). 56 (22.1%) subjects had a significant antibody decline and 35 (12.7%) had a low/borderline follow-up result. PCR positivity was lower in the falling (26.8% vs 52.8%, p = 0.001) and low/borderline (17.1% vs 51.9%, p < 0.001) antibody groups, as was the rate of ECG abnormalities. Falling and low/borderline antibody groups were predominantly composed of individuals with negative PCR and normal ECG findings: 64% and 71%, respectively. Conclusions/significance Low and falling antibody levels define a phenotype of possible spontaneous parasite clearance.